AYAT DAKWAH MENURUT LEMBAGA DAKWAH KOMUNITAS PP. MUHAMMADIYAH: (Analisis Maqasid Al-Qur’ân) - Zaeni, Ahmad (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This research discusses the understanding of LDK PP. Muhammadiyah regarding the verses of da'wah using the perspective of Maqâsid al-Qur'ân. According to LDK PP. Muhammadiyah, Da'wah based on the verses of the Koran stands on two functions of the Koran, namely message and grace. The use of the term mercy function in this case is very close to one of the terms Maqâsid al-Qur'ân, namely rahmah. Starting from this research problem, the researchers traced the intersection of the two functions with the theory of Maqâsid al-Qur'ân, then the researchers formulated the structure of the Maqâsid verses of da'wah in the LDK PP version. Muhammadiyah. The data analysis methods used are the istiqrâ’ (inductive method) and the muqâranah (comparative method). The inductive method was used to inventory the understanding of da'wah verses as a typical Maqâsid view in the LDK PP version. Muhammadiyah, while the comparative method is used to compare the understanding of da'wah verses of the LDK PP. Muhammadiyah with the formulation of Maqâsid al-Qur'ân. This research produced two findings. Firstly, by using the perspective of Maqâsid al-Qur'ân, secondly, the function of the Qur'anic verses of da'wah in the LDK PP version. Muhammadiyah is the dynamics of the mufassir maqâs}idi version of the Maqâsid formulation of da'wah verses, in the form of maqs}ad al-rahmah and maqsad al-risâlah with their respective derivatives. Second, the dynamics of understanding LDK PP. Muhammadiyah regarding da'wah verses shows two Maqâsid simultaneously, namely theocentric and anthropocentric Maqâsid with renewal in its applicable context.